Change in WHO cardiovascular risk prediction over three years in PLWH on efavirenz-based ART - Mahanani, Melani Ratih; Rambiki, Ethel; Kumwenda, Tapiwa; Wallrauch-Schwarz, Claudia; Heller, Tom; Winkler, Volker; Neuhann, Florian; Steffen, Hans Michael (Southern African journal of HIV medicine, 2025)
No abstract available.